Development of a Stable TiO2 Nanocomposite Self-Cleaning Coating for Outdoor Applications - F. Madidi; G. Momen; M. Farzaneh (Advances in Materials Science and Engineering)
A convenient and low-cost approach for the elaboration of a stable superhydrophobic coating is reported, involving the use of TiO2 nanoparticles via the spray coating method. This method can be used for preparing self-cleaning superhydrophobic coatings on large areas for different kinds of substrates. The synergistic effect of the micro/nanobinary scale roughness was produced by a multilayer RTV SR/TiO2 composite. The influence of the nanofiller concentration in a specific frequency range (40 Hz to 2 MHz) on the dielectric behavior was analyzed as well. It was found that the real relative permittivity (εr′) increases as the nanofiller concentration increases. Superhydrophobic behavior is analyzed by contact angle measurements, scanning electron microscopy (SEM), and profilometer. The stability of the developed coating also has been evaluated in terms of immersion in various aqueous solutions, heating, adhesion, and exposure to UV irradiation, and the results showed good stability against these factors. The coating retained its superhydrophobicity after several days of immersion in solutions of different pH levels (2, 4, 6, and 12) and different conductivities. In addition, they also exhibited exceptional stability against UV radiation and heating, as well as good mechanical stability.